Alat Penala Kendali Proporsional Pada Robot Line Follower Berbasis Website - Romdhon, Taufik Pathu; Rosyadi, Imron; A.S, Putra Wisnu; Hasad, Andi (Journal of Students‘ Research in Computer Science, 2021)
This research is about the proportional control value tuning tool on line follower robots or mobile robots. A mobile robot is one type of robot that can move, where the robot system can move itself from position A to position B, and the two positions are separated by a certain distance (the whole body of the robot moves), it can be said that the robot moves dynamically. Speed regulation on the robot requires a control system, one of which is a proportional control system. Proportional control is a control that has an output that is proportional to the magnitude of the error signal the difference between the desired quantity and the actual value. Tuning the proportional constant value using a website server that is created in realtime without the need to re-burn the program code in the line follower robot microcontroller. System testing on this tuning device is carried out to determine the delay time and the difference in delivery speed when using a mobile phone cellular network with a Wi-Fi network. At the time of testing the wemos system, the longest delay was 09.50.0 and the fastest was 00.000.8.